Pengaruh Perawatan Preventif Lifetime Baterai Lead Acid Untuk Persinyalan Kereta Api Listrik - Al Fath Rizki Fajari; Muhammad Fahmi Arsyad; Ponco Hadi Prasteyo (Jurnal Teknik Transportasi, 2023)
Trains operate supported by many factors, one of which is signaling and telecommunications equipment. This equipment must get a continuous supply of electricity, so that train operations are safe and smooth. One way to protect the power supply is by installing a battery uninterrupted power supply (UPS), as a source of electrical energy storage as a backup. To keep the battery in optimal condition, 1 month, 3 months and 12 months preventive maintenance is carried out. Treatment 12 months, tested with the method coulomb counting with discharge against the battery up to 80% total wasted capacity, to get the value state of health battery. There are 54 batteries valve-regulated lead acid (VRLA) with a voltage of 2 V and a nominal capacity of 200 Ah, which is connected in series with the voltage cut off 1.85 V. The results of preventive maintenance are seen by testing discharge battery at station A, namely the SoH condition where all the batteries are above the value of 80%, while at station B there are 5 batteries with SoH values ​​of 78%, 80%, 58%, 74%, and 72%, so the batteries must be replaced at fifth batteries with SoH rating of 80% and below.